Analysis Of Fixed Financing, Profit Sharing Financing And Non Performing Financing On Profit Gain Of Banking Industries In Indonesia - Loso Judijanto; Anggita Permata Yakup; Joko Rianto; Eha Hasni Wahidhani; Donny Dharmawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to determine whether profit-sharing, fixed financing, and non-performing financing (NPF) all have an impact on sharia banking earnings at the same time. Influence analysis research is what this study is doing. Purposive sampling was used in this study's sample process. The research sample in this study is sharia banking profit. Twenty Indonesian commercial banks that follow sharia law served as the study's population. This study employs quantitative data methodologies, meaning that Ordinary Least Squares analysis is employed to turn the research's data into numerical values. The research findings indicate that sharia banking earnings are significantly impacted by profit sharing, fixed financing, and non-performing financing (NPF) variables all at the same time. The profit-sharing component significantly and favorably affects profit. This implies that profit will rise with each increase in profit sharing. The profit margin is significantly and favorably impacted by fixed finance variables. This implies that profit will rise with each increase in fixed funding. The variable of non-performing finance (NPF) has a noteworthy and adverse impact on earnings. This implies that earnings will decrease with each increase in NPF. The modified R-squared value indicates that while some variation in the independent variables can be used to partially explain the variation in the dependent variable (profit), other variables unrelated to the variables under study account for the remaining portion.